Suppression of neuropeptide by botulinum toxin improves imiquimod-induced psoriasis-like dermatitis via the regulation of neuroimmune system. Issue 1 (January 2021) - Amalia, Syahla Nisaa; Uchiyama, Akihiko; Baral, Hritu; Inoue, Yuta; Yamazaki, Sahori; Fujiwara, Chisako; Sekiguchi, Akiko; Yokoyama, Yoko; Ogino, Sachiko; Torii, Ryoko; Hosoi, Mari; Ishikawa, Osamu; et al.
Highlights: BTX-B suppresses the progression of psoriasis-like dermatitis in IMQ-treated mice. BTX-B suppressed the type 17 inflammation in IMQ-treated skin lesions. BTX-B regulates psoriasis via neuroimmune system. Neuropeptide inhibitor, including BTX can be applied to the treatment of psoriasis. Abstract: Background: Psoriasis is a multifactorial disease arises from a complex interaction of genetics, immune system, and environmental aspects. IL-23/Th17 immune axis has been considered as a primary modulator in psoriasis. In addition, several findings imply that nervous system may take a part in the pathogenesis of psoriasis, suggesting that nervous system, through its neuropeptide, may interact with immune system and lead to the formation of psoriasis. Objective: We aimed to ascertain the role of neuropeptides secreted from neurons in the pathogenesis of psoriasis in vivo. Methods: The release of neuropeptide was inhibited by injecting Botulinum toxin B (BTX-B) on Imiquimod (IMQ)-induced psoriasis-like dermatitis mice model. Quantification of skin dermatitis, infiltrating inflammatory cells, and the production of cytokines at the lesional skin area were performed by PSI score, immunostaining, and real-time PCR. We also tested the effect of selective CGRP antagonist (CGRP8−37 ) on psoriasis-like dermatitis in IMQ-treated mice. Results: BTX-B injection significantly suppressed PSI score and reduced the number of CD4 + T cells, CD11c + dendritic cells, and the production of IL-17A/F in the lesional skin. The expressions of PGP9.5 + nerve fibers and neuropeptides (SP, CGRP) were also significantly reduced following BTX-B injection. Additionally, CGRP antagonist also suppressed the development of IMQ-induced psoriasis-like dermatitis in mice. Conclusion: The suppression of neuropeptide secretion in the skin by BTX injection might inhibit nerve elongation, the infiltration of immune cells, as well as IL-17 production, resulting in the improvement of psoriasis. Neuropeptide inhibitor could also be applied to the treatment of psoriasis.